Artificial Intelligence & Machine Learning in Design and Assessment of Structures - Markou, George; Bakas, Nikolaos P. (My University, 2021)
The use of Artificial Intelligence (AI) and Machine Learning (ML) algorithms in developing predictive models towards the design and assessment of structures is gaining significant momentum. This minisymposium aims to serve as an ideas exchange hub that will help scientists to share their current research work on AI and ML algorithms that have as a main objective the development of: 1. algorithms for automatic extraction of closed form design formulae, 2. machine learning models for the assessment and design of structures and materials, 3. data analytics, visualization and interpretation algorithms dealing with the mechanical behaviour of structures One of the main objectives of this minisymposium is to generate a broad discussion on how AI and ML algorithms can be utilized in assisting towards establishing a safer built environment in both low and high seismically active countries.
Keywords: Machine Learning; Structures; Design; Assessment